2013
DOI: 10.2337/dc12-2653
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Metabolic Syndrome and Diabetes Among Young Twins and Singletons in Guinea-Bissau

Abstract: OBJECTIVETwins in Africa may be at increased risk of metabolic disorders due to strained conditions in utero, including high exposure to infections. We studied metabolic syndrome (MS) and diabetes mellitus (DM) among young twins and singletons in Guinea-Bissau.RESEARCH DESIGN AND METHODSThe study was cross-sectional and occurred from October 2009 until August 2011 at the Bandim Health Project, a demographic surveillance site in the capital Bissau. Twins and singleton controls between 5 and 32 years were visite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…No difference was found in mean HbA1c either. Yet, as in the present investigation, higher fasting glucose and higher IFG prevalence were found in twins [ 26 ]. Adjusting for potential confounders such as age, sex, WHR and season caused the association between twin status and IFG to become even stronger.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…No difference was found in mean HbA1c either. Yet, as in the present investigation, higher fasting glucose and higher IFG prevalence were found in twins [ 26 ]. Adjusting for potential confounders such as age, sex, WHR and season caused the association between twin status and IFG to become even stronger.…”
Section: Discussionsupporting
confidence: 69%
“…We did not have data regarding insulin sensitivity or beta cell function during the OGTTs. In the previous study, no difference was found in fasting insulin or HOMA insulin resistance between twins and singletons [ 26 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Seventy six articles were included in the nal analysis in this meta-analysis. Twenty ve studies were excluded due to the following exclusion criteria: different study population [109][110][111][112][113], no full test [114][115][116][117], unclear diagnostic criteria [118][119][120][121][122][123][124][125], letter to editor [126], written in non English language [127,128], and different study design [129][130][131][132][133] (Fig. 1).…”
Section: Selection Of Eligible Studiesmentioning
confidence: 99%